El reglamento interior de la Universidad Central de 1853 - Martínez Neira, Manuel (CIAN-Revista de Historia de las Universidades, 2009)
Resumen: En 1853 el gobierno aprobó un reglamento interior para la Universidad Central inédito hasta ahora. Además de su edición, el trabajo indaga en la naturaleza de los distintos reglamentos que se sucedieron a lo largo del siglo XIX, la personalidad de su autor (el marqués de Morante, rector de la Universidad) y algunas claves de lectura del texto.Palabras clave: Marqués de Morante, Universidad Central.Abstract: In 1853, the Spanish government sanctioned the bylaws of its Central University, document that had remained unpublished until now. These bylaws are published in this article that, in addition, researches the character of their author, the Marquis of Morante (then Chancellor of the university), as well as the nature of the different bylaws that the University had along the nineteenth century, and it explains key aspects of the original document.Key Words: Marquis of Morante, Central University.